Enhance Parameter Speed Estimation of Induction Motor Using Modified Voltage Model Flux Estimation - Aryza, Solly; lubis, zulkarnain (Jurnal Elektro dan Telkomunikasi; Vol 7 No `1 (2020): Jurnal Teknik Elektro dan Telkomunikasi, 2021)
Enhance Parameter Speed Estimation of Induction Motor Using Modified Voltage Model Flux Estimation